Is short-course therapy enough at drug-resistant tuberculosis? - OGUN, HAMZA; OGUN, HAMZA; Ozmen, Ipek; Ozari Yildirim, Elif; Torun, Tulay; Calisir, Haluk Celalettin (My University, 2018)
Introduction: Tuberculosis drug resistance can be assessed by physicians with different approaches on issues such as the choice of treatment protocol and duration of treatment.